2018
DOI: 10.4103/ijnmr.ijnmr_67_17
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the preceptorship program on self-efficacy and learning outcomes in nursing students

Abstract: Background:This study aimed to determine the impact of the preceptorship program on self-efficacy and learning outcomes and the association between self-efficacy and learning outcomes in nursing students.Materials and Methods:This quasi-experimental study was conducted on 112 nursing students in 2012–2013. The subjects were selected through convenience sampling from the School of Nursing and Midwifery of Shiraz University of Medical Sciences, Iran. The general self-efficacy scale and the perception of overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 30 publications
1
21
0
4
Order By: Relevance
“…Therefore, in this study, we found no direct effect between general self-efficacy and NPPB. However, general self-efficacy had an effect on the nursing practice environment, which has been demonstrated in many studies [52]. On the one hand, nurses with a high level of self-efficacy can better perceive the benefits of the nursing practice environment and can make full use of the benefits of the environment for themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this study, we found no direct effect between general self-efficacy and NPPB. However, general self-efficacy had an effect on the nursing practice environment, which has been demonstrated in many studies [52]. On the one hand, nurses with a high level of self-efficacy can better perceive the benefits of the nursing practice environment and can make full use of the benefits of the environment for themselves.…”
Section: Discussionmentioning
confidence: 99%
“…After analysis, the Cronbach's alpha value was 0.835. In this study, self‐efficacy for breast cancer screening was divided into three levels (10–20 = low, 21–30 = moderate and 31–40 = high) …”
Section: Methodsmentioning
confidence: 99%
“…In this study, self-efficacy for breast cancer screening was divided into three levels (10-20 = low, 21-30 = moderate and 31-40 = high). 23 The items were assessed with 4-point Likert response options from 1 = completely incorrect to 4 = completely correct. The total score was 40.…”
Section: Study Design and Questionnairesmentioning
confidence: 99%
“…11 Expert teaching also improved self-efficacy, which was associated with such learning outcomes as independence and confidence in applying what was learned. 27 Teaching people in the society and developing their knowledge and performance could also play a significant role in survival after cardiac arrest. 28 The American Heart Association (AHA) guidelines have also focused on educating the general public about CPR.…”
Section: Introductionmentioning
confidence: 99%